Prevalence of Severe Neurocognitive Impairment and Its Association with Socio-Demographics and Functionality Among Ugandan Older Persons: A Hospital-Based Study - Atim, Letizia Maria; Kaggwa, Mark Mohan; Mamun, Mohammed A; Ashaba, Scholastic; Maling, Samuel (Clinical Interventions in Aging, 2021)
Background: The prevalence of neurocognitive disorders, especially dementia, is rising due to an increase in longevity. Early detection and diagnosis of neurocognitive impairments are important for early interventions and appropriate management of reversible causes, especially by the primary health workers. However, this study aimed to determine the prevalence and associated factors of severe neurocognitive impairment among elderly persons attending a tertiary hospital in Uganda. Methods: This cross-sectional survey was conducted in a Ugandan hospital setting, where older adults go for treatment for their chronic health problems. Following the inclusion criteria, interviews were conducted, where information about socio-demographics was collected, whereas neurocognitive impairment and functionality were assessed by Mini-Mental State Examination and Barthel Index, respectively. Chi-square test, Pearson correlation test, and logistic regression were performed to determine the factors associated with severe neurocognitive impairment. Results: A total of 507 elderly persons aged 60 years and above were enrolled in this study (mean age 68.62 ±7.95 years), and the prevalence of severe neurocognitive impairment was 28.01%. Advanced age, female gender, lower education level, and functional dependency were significantly associated with severe neurocognitive impairment. Conclusion: Severe neurocognitive impairment is prevalent among Ugandan hospital attending elderlies with functional dependency. This suggests a need to routinely screen cognitive disorders among older persons who visit the healthcare facilities with other physical complaints to enable early detection and treatment of reversible causes of neurocognitive impairment, such as depression and delirium to enable better functionality.
Keywords: Dementia; Neurocognitive disorder; Functionality; Prevalence and associated factors; Early diagnosis; Barthel Index; Mini-Mental Status Examination; Ugandan elderly